Meronce Manik-Manik Meningkatkan Kemampuan Motorik Halus Balita dengan DDST Caution - Pratiwi, Gita Sabrina; Nani, Desiyani (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Background: Children aged 3-5 year fall into the preschool stage, characterized by distinctive traits. At this age, they are in the psychosocial development stage of initiative and guilt. Children in this stage tend to engage in imaginative play, demonstrate creativity, show initiative in play, and learn new skills through games. Children with DDST Caution exhibit a delay in age-approproate developmental milestone. Objective: This case study was conducted to illustrate the implementation of constructive bead stringing play therapy on the improvement of fine motor skills in toodlers with DDST caution. Method: an observational study was conducted to investigate perceived behavior control among nurses working in ward setting. A total sampling technique was applied to recruite 47 nurses work in pediatric ward. Univariate analysis was utilize. Results: DDST assessment results indicated cautionary interpretation due to failures in fine motor aspects. After implementing constructive play therapy twice, there was an improvement in fine motor skills. The children showed enhanced fine motor skills in finger usage, hand precision, hand-eye coordination, and outcomes of the activities Conclusion: The results of the implementing constructive bead stringing play therapy showed an improvement in the fine motor skills of children, particulary in finger usage, hand precision, hand-eye coordination during movements, and the outcomes activities.